Status of mushroom production - Sharma, V P; Janakiram, T; Gautam, Yogesh (Indian Horticulture, 2020)
Mushroom is an excellent source of dietary components such as protein, vitamins, minerals, folic acid, carbohydrates, and low in fat. Mushroom industry in India is gaining momentum as an efficient and economically viable process for converting lignocelluloses residue into high-quality protein food. Mushrooms have immense nutritional and health benefits. The economic importance of mushrooms is also great for the farmers and they are highly proteinaceous. Each mushroom has a constituent which is extensively nutritional or medicinal in nature.